Comparative analysis of the prerequisites of the political processes of the “Arab Spring” - Курпебаева Г.К. (Әл-Фараби Атындағы Қазақ Ұлттық Университеті хабаршы шығыстану сериясы, 2019)
The article discusses the causes of the “Arab Spring”, and the factors influencing the escalation of the political crisis in Arab countries. As a result of a deep socio-political crisis in 2011–2013, in some countries of Middle East and North Africa there was a change of political regimes. Despite the preconditions of destabilization of authoritarian regimes, their forced change led to a crisis in some Arab states. The Middle East and North Africa took part in a forced revolutionary transformation of political regimes, called the Arab Spring. The growth of protests in the region is due to internal and external reasons, and in each country they depend on the specific socio-political, economic, religious situation and the peculiarities of the historical development of states. The consequences of these protests have led to destabilization in some countries of the Middle East. The purpose of this article is a comparative analysis of the main parameters of the Arab Spring Revolution. The methodological basis of the study is a systematic approach to the analysis of the complex and controversial interaction of economic, social and political processes. The theoretical significance of the study is determined by a comprehensive study of the causes and consequences of revolutionary events. The practical significance of the study lies in the possibility of using the results of work when writing textbooks for students and undergraduates of the specialty “International Relations and Regional Studies”, as well as for preparing reference books on political processes in the Middle East. Key words: Arab spring, authoritarian regime, the democratic forces, the escalation of the crisis, geopolitical dominance, transformation of the regime, the concept of modernization, the people’s power.